Fundamental liberties in relation to emergency and security laws in Malaysia / Norsham Ishak - Ishak, Norsham (Faculty of Law, 1985)
The topic is not a new area in the law of Constitution. Various writers have discussed thoroughly the concept of fundamental liberties, from theoritical to practical asrects, but an intimate discussi')n iu relati.on specifically to the Emergency and Security laws have been left to critism and still hanging in a loop area. To enhance this, the writer is interested to advance the development of the law in the country. The writer intends to analyse the use of the general phrase 'fundamental right' in part B of Chapter One. To consider when such a use is appropriate and how it may be justified in serious discourse about the nature and content of legal systems